MENGENAL DIRI DALAM AL-QUR’AN: Sukardi Bay - Sukardi Bay (STAI Darussalam Lampung, 2022)
This article discusses self-knowledge in the perspective of the Qur’an. The Qur’an as the main source of Islam, has clearly discussed human nature as stated in various chapters of the Qur'an. It was found that the concept of self in the Qur'an is understood by paying attention to humans themselves who point to each other, namely basyar, al-ins, al-insan, al-nas, and the bani Adam. Basyar has always been associated with traits that show human physiological significance, such as its origin from clay or dry clay. Also refers to the human aspect that has lust, has a tendency to eat, drink, trade, as well as a tendency to fulfill matters related to relationships (biological). Al-ins or humans called by God are good by nature. Al-insan is always associated with psychological or spiritual humans as creatures who think, give knowledge, and carry out the mandate. Also beings who become (becoming) and continue to move forward towards perfection. The essence of al-nas is that every human being must carry out activities related to society because in essence humans are social beings who need each other, even though they are created with different characteristics. The form of implementation can be done in the surrounding community, such as communicating and interacting with other humans, getting to know each other, helping each other, maintaining friendship, advising each other and so on. The goal is solely because of worship to Allah SWT. While the bani Adam which is also contained in the Qur'an refers to humans, in the sense of Adam's descendants. In other words, all human beings are members of one frame, because all originally came from the same essence.